"Wenn der Sprache Grenzen gesetzt werden" - eine wahrnehmungsdialektologische Untersuchung im Fränkischen und Thüringischen an der ehemaligen deutsch-deutschen Grenze - Sauer, Verena 1989- (2017)
This text is about the former inner-German state border between Thuringia and Bavaria inside the border regions of the "Eastern Franconian" language area and its effect on the spoken dialectic varieties. The main focus is not to research dialectgeographical dissimilarities between the border areas in former East Germany and West Germany as already explored (Lösch 2000, Fritz-Scheuplein 2001, Harnisch 2015) but to show perceptual linguistic concepts in the minds of linguistic laymen. The central question in this article is which salient dialect markers do the informants discern and use to locate a speech sample to a certain area inside the "Eastern Franconian" language area. Which salient dialect markers exist in informants perception about the varieties in former East German and West German border areas? Do they perceive a new linguistic variety border at the former political border between German Democratic Republic and Federal Republic of Germany?